Faceoff Fall Out - Jake Maddox (Stone Arch Books, 2018)
Jackson "Jax" Kingsford is a skilled hockey player with a wicked slapshot. When his team makes it to the state hockey tournament, he can't believe that he has to play against his former best friend, Archer Voss. The two were once inseparable and loved playing hockey together, both in Jax's backyard and on the school's hockey team. But then Archer's family had to move, splitting up the team and causing a fall out in their friendship. What will happen when the former friends face off against each other in the big game? Combining a high-stakes sports story with a dynamic full-color comic format, this Jake Maddox Graphic Novel is sure to be a win for young athletes and struggling readers alike.
Keywords: Sports Stories -- Sports Stories